Programa de seguridad laboral para el laboratorio de plasmas para energía de fusión y aplicaciones en el Tecnológico de Costa Rica - Gómez-Leiva, María Gabriela (Instituto Tecnológico de Costa Rica, 2014)
This project was developed in the Laboratory of Plasma for Fusion Energy Applications at Tecnológico de Costa Rica, it has approximately 25 contributors, among which researchers and students engaged in various projects. The main processes that take place are referred to research nuclear fusion, magnetic confinement devices, plasmas and industrial waste treatment. To carry out the project started with a detailed identification of hazards for each process and equipments, then a respective assessment of each risk group and with the help of various tools and regulations, Occupational Safety Program was created, since the laboratory for about seven years it has developed its investigations without a formal document that standards for all security features relating to each of its processes. In addition, were established alternatives of control engineering and administrative, to promote improvements in the areas of job safety, all with the purpose of raising awareness on the issue of accident prevention, which subsequently can incur serious offenses that affect the optimum functioning of the Laboratory of Plasmas.
Proyecto de Graduación (Bachillerato en Ingeniería en Seguridad Laboral e Higiene Ambiental) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Seguridad Laboral e Higiene Ambiental, 2014.
Keywords: Magnetismo; Seguridad; Incendios; Fuerza nuclear; Tecnología nuclear; Prevención de accidentes